Emotion dysregulation and impulsivity as overlapping symptoms in adult Attention-Deficit/Hyperactivity Disorder and Borderline Personality Disorder: severity profiles and associations with childhood traumatization and personality functioning - Eszter Kenézlői; Lívia Balogh; Szilvia Somogyi; Evelyn E. Lévay; Zsuzsa Halmai; Zsófia Nemoda; Zsolt S. Unoka; János M. Réthelyi (Annals of General Psychiatry)
Abstract Background Increased levels of emotion dysregulation and impulsive behavior are overlapping symptoms in adult Attention-Deficit/Hyperactivity Disorder (aADHD) and Borderline Personality Disorder (BPD), both symptom domains reflecting on inhibitory control, although from different angles. Our aims were to describe their differences in the above conditions, investigate their associations with childhood traumatization, and to explore the potential mediation of emotion dysregulation and impulsivity between childhood traumas and personality functioning. Methods Young adults between 18 and 36 years diagnosed with aADHD (n = 100) and BPD (n = 63) were investigated with structured clinical interviews, while age-matched healthy controls (n = 100) were screened for psychiatric disorders. Patients with aADHD-BPD comorbidity were excluded from further analyses. The Difficulties in Emotion Regulation Scale, the Barratt Impulsiveness Scale, the Level of Personality Functioning Scale, and the Childhood Trauma Questionnaire-Short Form were administered to investigate trait measures and childhood traumatization, respectively. Behavioral impulsivity and delay aversion were assessed using selected tests of the Cambridge Neuropsychological Test Automated Battery, and a computerized decision-making paradigm based on the Rogers decision-making task, respectively. Results Significantly higher levels of emotion dysregulation and impulsivity were present both in the aADHD and BPD groups, however with different profiles. Waiting and stopping impulsivity was selectively higher among aADHD patients compared to healthy controls. The BPD group reported higher levels of emotion dysregulation in all domains, and demonstrated increased delay aversion among uncertain conditions in decision-making. Higher levels of childhood trauma were associated with emotion dysregulation, trait impulsivity, and delay aversion across groups. Emotion regulatory capacity played a significant mediating role between childhood traumatization and the level of personality functioning. Conclusions Inhibitory control profiles of the aADHD and BPD groups were divergent. Childhood traumatization was associated with lower levels of personality functioning in adulthood, independently of diagnosis, an effect mediated more by emotion dysregulation, rather than impulsivity. These findings have various clinical implications for the treatment of aADHD and BPD, including psychoeducation, pharmacological interventions, and psychotherapy targeting specific symptom domains.